Exploring factors that affect Kindergarten teachers’ use of picturebooks with gender non-conforming fictional characters - Kalaitzi, Christina (Journal of Psychological Perspective, 2024)
Kindergarten environments are critical settings for early socialization and development of gender perceptions. Teachers play a significant role in shaping children’s understanding of gender, as do the materials and media they introduce to the classroom. The aim of this study is to explore the factors that affect kindergarten teachers’ use of picturebooks with gender non-conforming fictional characters in their teaching process. For the purposes of this research a quantitative approach was utilized. A sample of eighty-five kindergarten teachers answered a semi-structured questionnaire. A descriptive statistical analysis was performed, presenting the factors which affect kindergarten teachers’ use of gendered oriented picturebooks. Results show that factors which mostly affect kindergarten teachers are a) related to the educational framework, b) interwoven with teachers’ own personal beliefs, and c) referring to parents’ influence. The comparison of mean scores of factors in different academic qualification groups shows that highly qualified teachers with the least working experience are not affected negatively in their use of picturebooks with gender non-conforming characters in their teaching process. Those teachers are open to gender diversity, are not discouraged by the parents’ influence and take advantage of both the variety of LGBTQ picturebooks offered and the methodological framework of the Early Years Curriculum to deconstruct gender binaries. Mapping the factors could reveal the need for enhancing teachers’ continuing education on diversity matters and teachers’ resilience towards parents’ influence. Furthermore, findings reveal the need for designing a more detailed and practical methodological framework regarding the approach of gender issues in early years.